Else Øyen (ed.), Comparing Welfare States and Their Futures, Aldershot: Gower, 1986,246 s., 35 $; Richard Rose & Rei Shiratori(eds.), The Welfare State East and West, Oxford University Press, 1986, 213 s. - Damgaard, Erik (Politica, 1987)
-